Influence of carbonation on the low-temperature consolidation by Spark Plasma Sintering of carbonated calcium phosphate bioceramics. Issue 5 (1st April 2020) - Ortali, C.; Julien, I.; Drouet, C.; Champion, E.
Abstract: Calcium phosphates (CaP) such as biomimetic nanocrystalline apatite or amorphous calcium phosphate are hydrated bioactive compounds particularly suitable for bone repair applications due to their similarity with bone mineral. However, their consolidation in ceramic parts deserves special attention as they are thermodynamically metastable and can decompose into less bioactive phases upon heating. Adapted strategies are needed to obtain bulk bioceramics. Spark Plasma Sintering (SPS) has been shown to allow cold sintering of such compounds at temperatures like 150 °C while preserving the hydrated character and nanosized dimensions of the precursor powders. To this date, however, the role of the degree of carbonation of these precursors on the densification of CO3 -bearing CaP compounds via SPS has not been explored despite the natural carbonation of bone. In this work, several carbonated CaP hydrated compounds were prepared and consolidated by SPS and the characteristics of the obtained ceramics was scrutinized with respect to the starting powders. Two carbonation routes were carried out: via volume carbonation during powder synthesis or via subsequent surface ion exchange. All samples tested led to apatitic compounds after SPS, including amorphous CaP. We show that the degree of carbonation negatively affects the densification rate and propose possible hypotheses explaining this behavior. Evolution in the nature of the carbonate sites (apatitic A-, B-types and labile surface carbonates) before and after SPS is also noticed and commented. The consolidation of such compounds is however proven possible, and gives rise to bone-like apatitic compounds with great potential as bioactive resorbable ceramics for bone regeneration.